The Developmental nature of whisper in children - C.B, Prema Kumari (Journal of All India Institute of Speech and Hearing)
This study was conducted to learn as to how early children start whispering. It was expected that, there were no difference between males and females in this behavior. The responses from children were analysed together. The information from mothers and teachers on this behavior are presented separately and discussed.